Hadith #4627 - Sunan Abi Dawud - Jami' bin Abi Rashid جامع بن أبي راشد الكاهلي; Muhammad bin 'Ali bin al-Hanfiyyah محمد بن الحنفية; Muhammad bin al-Salt al-Basri محمد بن الصلت البصري; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
We used to say in the times of the Prophet (ﷺ): We do not compare anyone with Abu Bakr. ’Umar came next and then ‘Uthman. We then would leave (rest of) the companions of the Prophet (ﷺ) without treating any as superior to other.
Grade: Sahih